Availability, Accessibility, and Quality of Conservative Kidney Management Worldwide - Lunney, Meaghan; Bello, Aminu K.; Levin, Adeera; Tam-Tham, Helen; Thomas, Chandra; Osman, Mohamed A.; Ye, Feng; Bellorin-Font, Ezequiel; Benghanem Gharbi, Mohammed; Ghnaimat, Mohammad; Htay, Htay; Cho, Yeoungjee; et al. (Clinical journal of the American Society of Nephrology, 2021)
People with kidney failure typically receive KRT in the form of dialysis or transplantation. However, studies have suggested that not all patients with kidney failure are best suited for KRT. Additionally, KRT is costly and not always accessible in resource-restricted settings. Conservative kidney management is an alternate kidney failure therapy that focuses on symptom management, psychologic health, spiritual care, and family and social support. Despite the importance of conservative kidney management in kidney failure care, several barriers exist that affect its uptake and quality. The Global Kidney Health Atlas is an ongoing initiative of the International Society of Nephrology that aims to monitor and evaluate the status of global kidney care worldwide. This study reports on findings from the 2018 Global Kidney Health Atlas survey, specifically addressing the availability, accessibility, and quality of conservative kidney management. Respondents from 160 countries completed the survey, and 154 answered questions pertaining to conservative kidney management. Of these, 124 (81%) stated that conservative kidney management was available. Accessibility was low worldwide, particularly in low-income countries. Less than half of countries utilized multidisciplinary teams (46%); utilized shared decision making (32%); or provided psychologic, cultural, or spiritual support (36%). One-quarter provided relevant health care providers with training on conservative kidney management delivery. Overall, conservative kidney management is available in most countries; however, it is not optimally accessible or of the highest quality.